contestada

Use the linear combination method to solve the system of equations. *Explain each step of your solution.

2x - 3y = 13
x + 2y = 4

Respuesta :

Step 1: We have the next system of equations -

[tex]2x - 3y = 13[/tex]

[tex]x + 2y = 4[/tex]

Step 2: Now, we will multiply by -2 the second equation:-

[tex] - 2(x + 2y) = 4[/tex]

[tex]→ - 2x - 4y = - 8[/tex]

Step 3: Then we add it :-

[tex]2x - 3y = 13[/tex]

[tex]( + ) \: - 2x - 4y = - 8[/tex]

Step 4: After finding the sum, we simplify:-

[tex] - 7y = 5[/tex]

[tex]→y = - \frac{5}{7} [/tex]

Then, substitute the above y value to find x's value in any equation of Step 1. Now, I used to second equation in Step 1:-

[tex]x = - 2( \frac{ - 5}{7}) + 4[/tex]

Step 5: Then simplify :-

[tex]y = \frac{38}{7} [/tex]

Therefore, the final answer is :-

[tex]x = \frac{38}{7} [/tex]

and

[tex]y = \frac{5}{7} [/tex]

---------------------------------------------

Answered by Benjemin360 ☺️